Lipopolysaccharide Induces a Significant Increase in Expression of Iron Regulatory Hormone Hepcidin in the Cortex and Substantia Nigra in Rat Brain - Wang, Qin (The Endocrine Society, 2008)
Hepcidin plays an essential role in maintaining normal iron homeostasis outside the brain. This recently discovered iron regulation hormone is predominantly expressed in the liver, and regulated by iron and hypoxia. As an antimicrobial peptide, this hormone is also elevated during infections and inflammation. In this study we investigated the expression of hepcidin mRNA and protein in different brain regions, including the cortex, hippocampus, striatum, and substantia nigra, and the effects of lipopolysaccharide (LPS) on the expression of hepcidin using quantitative real-time RT-PCR and immunofluorescence analysis. Our data provided further evidence for the existence of hepcidin in all the regions we examined. We also demonstrated for the first time that LPS administration by iv injection can regulate the expression of hepcidin mRNA and protein not only in peripheral organs such as the liver, but also in the brain. LPS induced a significant increase in the expression of hepcidin mRNA and protein in the cortex and substantia nigra, but not in the hippocampus and striatum, indicating a regionally specific regulation of LPS on hepcidin in the brain. The relevant mechanisms and the functions of hepcidin in the brain remain to be elucidated.